SAT0241 Is there any nailfold capillaroscopic pattern in patients with primary sjögren's syndrome with or without raynaud's phenomenon and/or positive anti-RO/anti-LA?. (23rd January 2014) - Ortiz-Santamaria, V.; Corominas, H.; Castellví, I.; Moreno, M.; Morlà, R.; Clavaguera, T.; Erra, A.; Torrente, V.; Martinez, S.; Ordoñez, S.; Santo, P.; Reyner, P.; et al.
Abstract : Background: Nailfold capillaroscopy (NC) is a noninvasive technique that allows to scan the microcirculation. Tortuosities and isolated hemorrhages have been described in the NC of patients with primary Sjögren's syndrome (PSS). In patients with Raynaud's phenomenon (RP) associated with PSS decreased capillary density, greater presence of hemorrhage, enlarged loops and even megacapillaries have been reported. Objectives: 1) To identify specific findings in patients with PSS defined according to the American-European criteria of 2002. 2) To assess capillaroscopic differences in patients with PSS with or without RP. 3) To analise if the positive of anti-Ro and/or anti-La confers a distinct profile in capillaroscopy pattern. 4) To describe whether patients with labial biopsy findings characteristic of PSS have differentiated features in microvascular examination. Methods: The multicenter NC group of the Catalan Rheumatology Society (CapiCAT group), conducted 150 NC in patients with Sjögren's syndrome, 136 of them were diagnosed of PSS. Mean age was 57.6 years (±12.7), 130 (96%) were women. The mean time since PSS diagnosis was 7.9 years (±6.7). Demographic variables, presence of RP, symptoms of PSS, ANA, reumathoid factor, anti-Ro, anti-La, anti-CCP, salivary scintigraphy, labial biopsy, treatment and outcome of NC according to CapiCAT group consensus (capillary density, capillary length, tortuosities, capillary diameter - including enlarges loops and megacapilaries -, branching, capillary organisation, pericapillary hemorrhages, capillary thrombosis, areas of capillary loss, subpapillary venous plexus and capillaroscopic pattern) were collected. Results: RP was present in 32% of PSS, keratoconjunctivitis sicca in 91% (125/136) of patients (p<0.001), oral xerosis in 93% (127/136), skin or genital xerosis in 53% (72/136). Extraglandular involvement (arthritis, pneumonitis, blood disorders, peripheral neuropathy or CNS involvement) was associated in 47% (65/136). 75% of PSS were anti-Ro + (102/136) and 40% (54/136) anti-La +. In patients with positive anti-Ro and/or anti-La NC was normal in 53% of cases and nonspecific in 36% (p NS). Lip biopsy was characteristic of PSS in 45/50 lip biopsies. There were no difference in the findings of NC. NC in patients with PSS were normal in 51% of cases and nonspecific in 34%. Scleroderma pattern was reported in 14 patients. RP associated with PSS had nonspecific capillaroscopy in 40% of cases (p=0.1). The amount of pericapillary hemorrhages (p=0.06) and capillary thrombosis (p=0.2) were not increased in our patients, but more enlarged loops were detected in 48% (18/37) of cases. Conclusions: 1) Patients with positive anti-Ro and/or anti-La have not a distinct profile in capillaroscopy pattern. 2) Patients with labial biopsy findings characteristic of PSS have not differential features in microvascular examination. 3) In our sample, patients with RP associated with PSS had more enlarged loops, but neither pericapillary hemorrhagesnor capillary thrombosis were observed, as reported in the literature. Disclosure of Interest: None Declared